Activated carbon's adsorbent by agricultural wastes in textile waste water - Chin, Su Xian (2014)
Textile industry has caused harm and deterioration to the environment and also ecosystem due to the releasing of large amount of waste water into the environment. The treatment of this waste water has become one of the biggest challenges faced by textile manufacturers. One of the most suitable and low operational cost methods to remove contaminants such as heavy metals in textile waste water is by using activated carbon. The amount of 10 g of 0.6 mm granular activated carbon from coconut shells, oil palm shells, coconut fibers, oil palm fibers, coconut fronds, and oil palm fronds respectively has been successfully produced through chemical activation process using phosphoric acid. In this research, the activated carbon is used to analyze the adsorbent of selected heavy metals such as zinc, lead, and copper in textile waste water. The capability of adsorbent between activated carbon from coconut wastes and oil palm wastes in textile waste water were also compared in this research. Results indicated that oil palm fronds and coconut shells had shown high capability in adsorbing zinc, and lead metals in textile waste water due to their large surface area. Results have also indicated that oil palm fronds and coconut fibers adsorbed the most amount of copper metal due to their large surface area with high availability of exchangeable sites.